EXPERIMENTALSTUDY ON TREATMENTOF SAGO WASTEWATER USINGFIXEDBED REACTORIN THE PRENCE OF EFFECTIVE MICROORGANISMS (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
This study assesses the recital of fixed bed reactors in anaerobic treatment of sago industrywastewater using Effective Microorganism. A laboratory scales Up flow Anaerobic fixed bedreactor, having a working effective volume of about 13. L was operated and Polypropylenerings were used as packing media. The initial Hydraulic Retention Time range was about 0.6.days and further increased. Various effluent characteristics ranges of COD concentration,Total Suspended Solids, VFA, and biogas production were studied until the attainment ofsteady state. The Hydraulic Retention Time of a sago wastewater was 3.0, 1.50, 1.00, 0.75,0.60 days. The maximum COD removal efficiency of 83% was attained at a prefixed flowrate of 0.18 l/day with the average COD of 5320mg/l at 3.0 days HRT. It was accomplishedthat the influence of COD reduction was increase to increases the HRT The gas productionwas increased with increased OLR. The maximum gas production of 0.255 m3/kg COD infixed bed reactor in the presence of effective microorganisms was obtained.